Pondasi Sumuran Sebagai Solusi Pada Jenis Tanah Berpasir Dengan Muka Air Tanah Tinggi: Foundation Of Wells As A Solution For Sandy Soil Types With High Groundwater Levels - Hikmatul Lailiya; Agata Iwan Candra; Khoirun Nisa'; Rina Dwi Fatika; M Ilham Fauzil Fahmi; Ricky Putra Ardianto; Ogest Tegar Widyakrama (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Soil conditions have an important influence on foundation planning in shophouse construction. Sandy soil with a high groundwater table is a problem because it has a low bearing capacity and is difficult for foundation casting. The aim of the research is to plan a proper foundation. This research by taking samples for testing compaction and shear strength. The test results are used to analyze the existing foundation planning. If the bearing capacity value does not meet the load assumption of 100 t/m2, then a re-planning is carried out with a minipile well foundation. The results of the research show that the existing foundation is a palm type foundation and the bearing capacity value is not fulfilled. So that the modification of the well foundation in the form of a minipile was carried out and the soil carrying capacity was obtained at 36.61 t/m2. To be able to withstand the load of the structure, it is necessary to plan the use of 3 minipiles, so that a value of 109.82 t/m2 is obtained which indicates the foundation is suitable for use. The results of this study can be used as a reference for planning foundations with sandy soil conditions with a high water table.